An introduction to cultural anthropology - Seremetakis, C. Nadia (Constantina Nadia) (Cambridge Scholars Publishing, 2017)
This book engages young scholars, teachers and students in a critical dialogue with past and present directions in cultural-historical studies. More particularly, it prepares prospective anthropologists, as well as readers interested in human cultures for understanding basic theoretical and methodological ethnographic principles and pursuing further what has been known as cultural anthropological perspectives. The book discusses key, field-based studies in the discipline and places them in dialogue with related studies in social history, linguistics, philosophy, literature, and photography, am.